2009
DOI: 10.1073/pnas.0903958106
|View full text |Cite
|
Sign up to set email alerts
|

Blocking angiotensin-converting enzyme induces potent regulatory T cells and modulates TH1- and TH17-mediated autoimmunity

Abstract: The renin-angiotensin-aldosterone system (RAAS) is a major regulator of blood pressure. The octapeptide angiotensin II (AII) is proteolytically processed from the decapeptide AI by angiotensin-converting enzyme (ACE), and then acts via angiotensin type 1 and type 2 receptors (AT1R and AT2R). Inhibitors of ACE and antagonists of the AT1R are used in the treatment of hypertension, myocardial infarction, and stroke. We now show that the RAAS also plays a major role in autoimmunity, exemplified by multiple scleros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
263
4
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(282 citation statements)
references
References 33 publications
11
263
4
4
Order By: Relevance
“…Thus, it has been shown that deletion of immune cells or immune suppression therapy reduces Ang II-dependent hypertension and hypertensive end organ damage, respectively (3,4). In line with these results, recent studies have provided profound evidence that AT1 receptor inhibition directly affects immune cell function and thereby ameliorates the clinical course of experimental autoimmune encephalomyelitis (EAE) (5,6) or systemic lupus erythematosus (7,8).…”
supporting
confidence: 59%
“…Thus, it has been shown that deletion of immune cells or immune suppression therapy reduces Ang II-dependent hypertension and hypertensive end organ damage, respectively (3,4). In line with these results, recent studies have provided profound evidence that AT1 receptor inhibition directly affects immune cell function and thereby ameliorates the clinical course of experimental autoimmune encephalomyelitis (EAE) (5,6) or systemic lupus erythematosus (7,8).…”
supporting
confidence: 59%
“…Indeed, Kit W-sh/W-sh mice show cardiomegaly 30 and may also display spontaneous hypertension, a condition associated to Corin ablation 49 that may favor EAE development, as indicated by the recent observation that anti-hypertensive drugs suppress autoimmune response in EAE. 50 The Kit W-sh/W-sh mutation may also produce dysregulations in a series of genes included in the inverted region, whose effects in immunity are largely unknown. 30 Finally, the two c-Kit-mutated strains differ in their genetic background, and the WBB6F 1 -Kit þ / þ is characterized by higher number of peritoneal MCs and neutrophils than the C57BL/6-Kit þ / þ .…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells are a family of suppressor T cells which are further divided into two groups: thymicderived 'naturally occurring' Treg cells and induced/adaptive Treg cells generated extra thymically under certain conditions, including autoimmune diseases, transplantation tolerance and tumor immunity. [20][21][22] Accumulating evidence suggests that Treg cells induced in tumor microenvironments are highly immunosuppressive. 23 Relevant to antitumor immunotherapy, experimental models have shown that removal of Treg cells modifies the immune response to tumors.…”
Section: Cd8mentioning
confidence: 99%